Comparison of Corticomedullary Ratio and Medullary Rim Sign in Feline Lower Urinary Tract Disease Recurrence in Persian Breed - Wardhana, Analis Wisnu; Jihan, Putri; Suwardani, Gagas Wiratama (Jurnal Medik Veteriner, 2023)
The Persian cat breed has grown rapidly in the last decade. This increase is not balanced with adequate maintenance, especially related to feed management and this causes problems, one of which is the emergence of feline lower urinary tract disease (FLUTD). Several complications often occur in cases of FLUTD recurrence, one of which is the kidneys. This study aimed to determine the differences in the corticomedullary ratio (CMR) and medullary rim sign (MRS) using an ultrasonography (USG) in Persian cats with FLUTD recurrences. Kidney examination was carried out using a linear USG probe with a frequency of 10MHz, with a dorsal view of the kidney. The parameters were analyzed using the independent t-test. Based on the calculation results, it was found that there were no significant differences in CM and MRS values in cats with FLUTD and FLUTD recurrences. These results indicated that cats with FLUTD recurrences have slightly disorders in kidney tissue but it still did not affect the macro anatomy of the kidney, and might cause chronic kidney disease.